2021
DOI: 10.1007/s00167-021-06687-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional knee phenotypes of OA patients undergoing total knee arthroplasty are significantly more varus or valgus than in a non-OA control group

Abstract: Purpose The aim of this study was to analyse the coronal alignment of a large population of patients undergoing total knee arthroplasty using a modern classiication of the knee phenotypes found in a population of non-osteoarthritic individuals. Methods Five hundred and four navigated total knee arthroplasties were included in the OA group. The following angles were measured with a computer image-free navigation system: mechanical femorotibial angle measured on the medial side without stress and with maximum ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 26 publications
2
40
2
Order By: Relevance
“…The importance of the overall lower limb alignment is well recognized. However, the role of local parameters cannot be ignored [9, 10, 13]. Hirschmann et al proposed that there are 125 possible functional knee phenotypes and 45 were found in young non‐osteoarthritic patients, according to the overall lower limb alignment parameter (HKA angle) and the local parameters (MPTA and femoral mechanical angle) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the overall lower limb alignment is well recognized. However, the role of local parameters cannot be ignored [9, 10, 13]. Hirschmann et al proposed that there are 125 possible functional knee phenotypes and 45 were found in young non‐osteoarthritic patients, according to the overall lower limb alignment parameter (HKA angle) and the local parameters (MPTA and femoral mechanical angle) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hirschmann et al proposed that there are 125 possible functional knee phenotypes and 45 were found in young non‐osteoarthritic patients, according to the overall lower limb alignment parameter (HKA angle) and the local parameters (MPTA and femoral mechanical angle) [10]. Jenny et al found a wider distribution of the phenotypes in the osteoarthritic patients than in the non‐osteoarthritic patients [13]. Thus, it would be of great interest to assess a patient’s individual anatomy in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The following angles were measured with the navigation system prior to prosthetic implantation: medial femorotibial mechanical angle without stress and with maximum manual stress to reduce the deformation, medial distal femoral mechanical angle (MDFMA), medial proximal tibial mechanical angle (MPTMA). The native angles were derived from the osteoarthritic knee angles using a previously published technique [9]. The native medial distal femoral angle was defined as the MDFMA increased by 2° for varus deformities or decreased by 2° for valgus deformities to compensate for degenerative wear of the femoral cartilage [16].…”
Section: Methodsmentioning
confidence: 99%
“…Based on this analysis, the authors identified common coronal knee phenotypes and observed that mechanical, anatomical and restricted kinematic alignment matched phenotypes in only 5%, 20% and 51% of the non-osteoarthritic population, respectively. In fact, recent studies have shown that knee phenotypes undergoing total knee arthroplasty are very heterogeneous and are significantly more in varus or valgus than in a control group without OA [ 6 , 10 ]. These results support the fact that one alignment strategy does not suit all patients and a more personalised approach should be considered.…”
Section: Introductionmentioning
confidence: 99%